Asuhan Kebidanan Continuity of Care (Coc) pada Ny. P Umur 28 Tahun di Puskesmas Kalikajar 2 - Imbuh; Luvi Dian Afriyani (Universitas Ngudi Waluyo, 2026)
Continuity of Care (CoC) in midwifery refers to the provision of comprehensive care from pregnancy, childbirth, postpartum, and neonatal periods until the mother decides to use a family planning method. This approach aims to monitor and detect potential complications affecting both mother and baby from pregnancy through family planning utilization. The objective of this case study was to provide comprehensive midwifery care to Ny.P at Kalikajar 2 Community Health Center, Wonosobo. This case study was conducted on Ny.P, a 28-year-old woman with obstetric status G2P1A0, at Kalikajar 2 Community Health Center. Antenatal care was provided through six visits with monitoring based on the 10T standard. Delivery was performed by cesarean section due to severe preeclampsia at Adina Mother and Child Hospital. A male infant was born weighing 2,790 grams, with a body length of 48 cm, and cried spontaneously immediately after birth. The postpartum and neonatal periods progressed normally without signs of infection or other complications. Following delivery, the mother chose to use an intrauterine device (IUD) as her contraceptive method. In conclusion, the comprehensive midwifery care provided demonstrated that the cesarean section was performed according to medical indications and Evidence-Based Midwifery guidelines. Continuous and comprehensive care contributed to the mother's recovery and helped prevent further complications. Abstrak Asuhan kebidanan berkelanjutan (Icontinuity of care) yaitu pemberian asuhan kebidanan sejak kehamilan, bersalin, nifas, neonatus hingga memutuskan menggunakan KB ini bertujuan sebagai upaya membantu memantau dan mendeteksi adanya kemungkinan timbulnya komplikasi yang menyertai ibu dan bayi dari masa kehamilan sampai ibu menggunakan KB. Tujuan penelitian adalah melakukan asuhan kebidanan komprehnsif pada Ny. Di Puskesmas Kalikajar 2 Wonosobo. Studi kasus ini dilakukan pada Ny.P usia 28 tahun G2P1A0 di Puskesmas Kalikajar 2. Asuhan kehmilan diberikan sebanyak 6 kali dengan pemantauan standar 10 T. Persalinan dilakukan melalui tindakan secio caesare atas indikasi Preeklamsi Berat di RSIA Adina. Bayi lahir dengan jenis kelamin laki-laki, BB 2790 gr, panjang badan 48 cm, dan langsung menangis. Masa nifas dan neonatus berjalan normal tanpa tanda-tanda infeksi atau komplikasi. Ibu menggunakan KB IUD pasca persalinan. Kesimpulan dari asuhan kebidanna komprehensif ini bahwa tindakan secio caesarea telah dilakukan sesuai dengan indikasi medis dan pedovan Evidance-Based Midwifery. Asuhan yang diberikan secara komprehensif membantu mempercepat pemulihan ibu dan mencegah komplikasi lebih lanjut.